Efficiency Analysis of Vegetable Production; An Appraisal of Tunnel Farming System in Punjab, Pakistan - Jaffar, Muhammad Mukhdoom Bin; Ramzan, Muhammad Javed; Ilyas, Muhammad; Munir, Saqib (Pakistan Journal of Humanities and Social Sciences, 2024)
In Pakistan, where traditional farming methods prevail, the potential benefits of tunnel farming remain unclear. To investigate, the study surveyed 353 farmers across five districts in Punjab, with 226 using tunnel technology and 127 employing conventional methods. Stochastic frontier analysis revealed that tunnel farmers demonstrated higher technical, economic, and overall efficiency compared to conventional farmers. Results indicated that tunnel farmers exhibit higher economic efficiency compared to conventional farmers, suggesting a potential 13% improvement in economic efficiency if conventional farmers transition to tunnel technology. Factors such as farm area, age, education, family size, irrigation, fertilizer use, and labour hours significantly influence technical inefficiency, highlighting the importance of these variables in enhancing farming efficiency. This efficiency stems from factors such as the use of hybrid seeds, advanced fertilizers, drip irrigation, and skilled labour, leading to increased output and extended market seasons. Despite these advantages, financial constraints hinder many farmers from adopting tunnel farming. By supporting the transition to tunnel farming, Pakistan can improve agricultural productivity, enhance food security, and uplift the livelihoods of its farming communities.